Social Media Strategy to Improve Brand Image: in the Context of Students’ Decision Making - Rini Adiyani; Muhammad Husin Nur Muzakki; Zandra Dwanita Widodo; Angga Ranggana Putra (Universitas Muhammadiyah Yogyakarta, 2021)
This study aims to examine and analyze the influence of social media on brand image and student decision-making. This study involved as many as 210 students from the health sciences and business studies program. Of the total 210 data obtained, the remaining 202 data can be used for further testing and data analysis, this is because there are a number of data that are categorized as outliers so that they must be eliminated. This study is a quantitative research category using a survey approach as a method of data collection. Then, regarding the process of testing and analyzing data, this study uses a structural equation modeling (SEM) approach with AMOS software. The findings of this study confirm that social media has a significant positive effect on brand image and decision making, besides that brand image has a positive and significant effect on student decision making. The findings of this study make a positive contribution to the development of science, especially in the field of marketing strategies through social media in improving brand image and decision making. The findings of this study are expected to make a practical contribution to increasing product competitiveness and consumer confidence.